2020
DOI: 10.1007/s10495-020-01625-1
|View full text |Cite
|
Sign up to set email alerts
|

In S. cerevisiae hydroxycitric acid antagonizes chronological aging and apoptosis regardless of citrate lyase

Abstract: Caloric restriction mimetics (CRMs) are promising molecules to prevent age-related diseases as they activate pathways driven by a true caloric restriction. Hydroxycitric acid (HCA) is considered a bona fide CRM since it depletes acetyl-CoA pools by acting as a competitive inhibitor of ATP citrate lyase (ACLY), ultimately repressing protein acetylation and promoting autophagy. Importantly, it can reduce inflammation and tumour development. In order to identify phenotypically relevant new HCA targets we have inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 73 publications
1
5
0
Order By: Relevance
“…These data suggest that the addition of phycocyanin at the end of the growth phase might favour survival through a mechanism other than hormesis, previously proposed to explain how an increase in ROS might, in the case of phycocyanin added at the time of inoculation, favour survival. It might be that phycocyanin added on day 0 of CLS (when maximum cell density is reached) acts on signalling mechanisms, as observed for hydroxycitric acid, a caloric restriction mimetic we previously investigated [37]. Genetic analysis on yeast CLS mutants indicated that part of the powerful anti-aging effects of hydroxycitrate can be sensed by Sch9 and Ras2, two conserved key regulators of nutritional and stress signal pathways of primary importance in S. cerevisiae [37].…”
Section: Effect Of Phycocyanin Added On Day 0 Of Cls When Maximum Cel...mentioning
confidence: 95%
See 1 more Smart Citation
“…These data suggest that the addition of phycocyanin at the end of the growth phase might favour survival through a mechanism other than hormesis, previously proposed to explain how an increase in ROS might, in the case of phycocyanin added at the time of inoculation, favour survival. It might be that phycocyanin added on day 0 of CLS (when maximum cell density is reached) acts on signalling mechanisms, as observed for hydroxycitric acid, a caloric restriction mimetic we previously investigated [37]. Genetic analysis on yeast CLS mutants indicated that part of the powerful anti-aging effects of hydroxycitrate can be sensed by Sch9 and Ras2, two conserved key regulators of nutritional and stress signal pathways of primary importance in S. cerevisiae [37].…”
Section: Effect Of Phycocyanin Added On Day 0 Of Cls When Maximum Cel...mentioning
confidence: 95%
“…It might be that phycocyanin added on day 0 of CLS (when maximum cell density is reached) acts on signalling mechanisms, as observed for hydroxycitric acid, a caloric restriction mimetic we previously investigated [37]. Genetic analysis on yeast CLS mutants indicated that part of the powerful anti-aging effects of hydroxycitrate can be sensed by Sch9 and Ras2, two conserved key regulators of nutritional and stress signal pathways of primary importance in S. cerevisiae [37]. However, it could not be excluded that the reduced ROS level observed when PC was added at the end of the growth phase could be simply explained by the lower concentration of PC present in the medium.…”
Section: Effect Of Phycocyanin Added On Day 0 Of Cls When Maximum Cel...mentioning
confidence: 97%
“…In addition, HCA seems to upregulate the genes encoding serotonin receptors and raise endogenous serotonin concentrations. These actions promote oxidation of fullness fat and lower de novo lipogenesis (Baroni et al, 2020).…”
Section: (-)-Hydroxycitric Acidmentioning
confidence: 99%
“…Interestingly, there is interplay between aging progression and secretion of secondary metabolites. These metabolites modulate the rate of aging, and may include sphingolipids (Ren and Hannun 2016 ), NADPH (Mohammad et al 2020 ), hydrogen peroxide (Dakik and Titorenko et al 2016 ), ethanol (Mohammad et al 2018 ), acetic acid (Baroni et al 2020 ), and hydrogen sulfide (Huang et al 2017 ), among others.…”
Section: Introductionmentioning
confidence: 99%
“…It is a model organism of choice due to its relatively short lifespan, well-characterized genome, and easy genetic engineering with myriad protocols readily available (Dakik et al 2020 ; Kaeberlein 2010 ). S. cerevisiae has become the most extensively used eukaryote in the study of aging (Arlia-Ciommo et al 2014 ; Bilinski et al 2017 ), cell cycle (Musa, et al 2018 ; Leonov et al 2017 ), gene expression (Postnikoff et al 2017 ; Ksiazek 2010 ), metabolism (Baccolo et al 2018 ; Croft et al 2020 ), signal transduction (Hohmann et al 2007 ; Babazadeh et al 2014 ), and apoptosis (Baroni et al 2020 ; Owsianowski et al 2008 ). Hence, to understand the complexity of organismal lifespan in a model organism (e.g., yeast S. cerevisiae ), aging studies are often designed to; (i) identify underlying causes of aging and in extension the associated physiological cellular damage it causes (ii) to devise strategies for the delay and possible reversal of aging development, (iii) and thirdly, to limit cell vulnerability to a wide range of aging inducing conditions.…”
Section: Introductionmentioning
confidence: 99%